2011
DOI: 10.5380/abpr.v40i(1-4).25203
|View full text |Cite
|
Sign up to set email alerts
|

<htm>Visitantes florais de <i>Opuntia monacantha </i>(Cactaceae) em restingas de Florianópolis, SC, Brasil</htm>

Abstract: htm>Visitantes florais de <i>Opuntia monacantha </i>(Cactaceae) em restingas de Florianópolis, SC, Brasil</htm>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…siqueira-filho & Machado (2001) noted that this flowering strategy consists of producing just a few flowers per day during a long period of time, which favors random cross-pollinations between individuals of different groups. a study by Lenzi & orth (2011) with O. monacantha in restinga areas on florianópolis Island demonstrated that the flowers of this species are frequently visited by different bee guilds and indicated that Cephalocolletes isabelae urban, 1995 (colletidae) is an oligolectic floral visitor and the principal pollinator of O. monacantha.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…siqueira-filho & Machado (2001) noted that this flowering strategy consists of producing just a few flowers per day during a long period of time, which favors random cross-pollinations between individuals of different groups. a study by Lenzi & orth (2011) with O. monacantha in restinga areas on florianópolis Island demonstrated that the flowers of this species are frequently visited by different bee guilds and indicated that Cephalocolletes isabelae urban, 1995 (colletidae) is an oligolectic floral visitor and the principal pollinator of O. monacantha.…”
Section: Resultsmentioning
confidence: 99%
“…The flowers are visited by insects such as bees, ants (Hymenoptera), and beetles (Coleoptera). The floral resource offered is pollen; nectar is absent (Lenzi & orth 2011). The hundreds of white stamen filaments each have yellow sagittate anthers.…”
Section: Study Areasmentioning
confidence: 99%
“…For example, Cyclocephala species are known to destructively feed on flowers of some crop plants (Remillet 1988, Posada Ochoa 1989) and the cactus species Echinopsis ancistrophora Speg. (Schlumpberger et al 2009) and Opuntia monocantha Haw (Lenzi and Orth 2011). …”
Section: Cyclocephalines As Floral Visitorsmentioning
confidence: 99%
“…Dicot families recorded as host plants include Asteraceae (Hayward 1946), Lecythidaceae (Prance 1976), and Cactaceae (Lenzi and Orth 2011).…”
Section: Discussionmentioning
confidence: 99%